2017
DOI: 10.1159/000481576
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Metastases from Breast Cancer: Managing the Unexpected. A Systematic Review

Abstract: Breast cancer (BrC) has the highest incidence among females world over and it is one of the most common causes of death from cancer overall. Its high mortality is mostly due to its propensity to rapidly spread to other organs through lymphatic and blood vessels in spite of proper treatment. Bladder metastases from BrC are rare, with 50 cases having been reported in the last 60 years. This review aims to discuss some critical points regarding this uncommon condition. First, we performed a systematic review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 58 publications
0
52
0
4
Order By: Relevance
“…Some authors reported differences in hormonal (ER and PgR) and HER2 expression between primary and metastatic tissue, with discordance rates ranging from 24 to 39% (6,12). Bladder metastases from BrC usually occurs a few months after the initial diagnosis of the primary tumour, but they might also occur years later (3,10). However, it is possible of bladder metastases being present at the time of first diagnosis of BrC, like in the case reported by Shah et al (8), whereby acute renal failure due to the ureteral obstruction was the presenting sign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported differences in hormonal (ER and PgR) and HER2 expression between primary and metastatic tissue, with discordance rates ranging from 24 to 39% (6,12). Bladder metastases from BrC usually occurs a few months after the initial diagnosis of the primary tumour, but they might also occur years later (3,10). However, it is possible of bladder metastases being present at the time of first diagnosis of BrC, like in the case reported by Shah et al (8), whereby acute renal failure due to the ureteral obstruction was the presenting sign.…”
Section: Discussionmentioning
confidence: 99%
“…BrC accounts for about 2.4% cases of all bladder metastasis (1). In most instances, bladder metastases from BrC are associated with other metastatic involvement of pelvic organ with a very poor survival (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…In this setting, primary tumors of the stomach, skin, and lung are the most common places of origin of these distant metastases 13. A recent systematic review conducted by Sanguedolce et al14 reported 54 cases of breast cancer with bladder metastasis. A retrospective study with 282 cases of secondary solid bladder tumors showed a prevalence of 2.5% of breast cancer metastasis 13.…”
Section: Discussionmentioning
confidence: 99%
“…Tableau : Caractéristiques cliniques de cas de métastases vésicales d'origine mammaire rapportés dans la littérature de 1950 à ce jour. RxT, xgeva, tamoxifène † = décès ; > = plus de ; 5-FU = 5-fluorouracile ; adénoC = adénocarcinome ; CC = carcinome canalaire ; CCI = carcinome canalaire invasif ; chimiotT = chimiothérapie ; CL = carcinome lobulaire ; CLI = carcinome lobulaire invasif ; CT = computed tomography ; HER2 = human epidermal growth factor receptor 2 ; MM = multimétastatique ; ND = Non disponible : article original non disponible, information via citation(s) ; NR = Non renseigné : informations non présentes dans l'article ; PET-CT = positron emission tomography-computed tomography ; RH = récepteurs hormonaux ; RMN = résonance magnétique nucléaire ; RO = récepteurs aux oestrogènes ; RP = récepteurs de la progestérone ; Rx = radiographie ; RxT= radiothérapie Les cytokératines CK7 et CK20 seront aussi cherchées avec un marquage doublement positif orientant vers une origine vésicale et un marquage CK7 positif et CK20 négatif orientant autant vers la vessie que le sein 53 . L'expression de p53 et p40 orientera par contre plutôt vers une origine vésicale 54 , ainsi que l'expression de la béta-caténine 55 .…”
Section: Discussionunclassified